2006
DOI: 10.1124/jpet.106.113357
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine2C Receptor Contribution to m-Chlorophenylpiperazine and N-Methyl-β-carboline-3-carboxamide-Induced Anxiety-Like Behavior and Limbic Brain Activation

Abstract: Activation of 5-hydroxytryptamine2C (5-HT 2C ) receptors by the 5-HT 2 receptor agonist m-chlorophenylpiperazine (m-CPP) elicits anxiety in humans and anxiety-like behavior in animals. We compared the effects of m-CPP with the anxiogenic GABA A receptor inverse agonist N-methyl-␤-carboline-3-carboxamide (FG-7142) on both anxiety-like behavior and regional brain activation using functional magnetic resonance imaging (fMRI) in the rat. We also determined whether the selective 5-HT 2C receptor antagonist SB 24208… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 42 publications
4
47
0
Order By: Relevance
“…The current results are consistent with prior work indicating that an acute increase in 5-HT is associated with anxiety (Abrams et al 2005;Graeff et al 1996;Hackler et al 2007;Lowry et al 2005) and can interfere with escape behaviors (Brown et al 1982). Additionally, anxiety-like behaviors have been reported following a single administration of an SSRI in several other animal models of anxiety including social interaction (Bagdy et al 2001;, the elevated plus maze (Kurt et al 2000), and the free-exploration test (Belzung et al 2001).…”
Section: Fluoxetine-induced Behaviorssupporting
confidence: 90%
See 1 more Smart Citation
“…The current results are consistent with prior work indicating that an acute increase in 5-HT is associated with anxiety (Abrams et al 2005;Graeff et al 1996;Hackler et al 2007;Lowry et al 2005) and can interfere with escape behaviors (Brown et al 1982). Additionally, anxiety-like behaviors have been reported following a single administration of an SSRI in several other animal models of anxiety including social interaction (Bagdy et al 2001;, the elevated plus maze (Kurt et al 2000), and the free-exploration test (Belzung et al 2001).…”
Section: Fluoxetine-induced Behaviorssupporting
confidence: 90%
“…Anxiety-like behavioral effects of anxiogenic drugs such as the 5-HT 2 receptor agonist m-chlorophenylpiperazine and the GABA A receptor partial inverse agonist Nmethyl-beta-carboline-3-carboxamide correspond with activation of DRN 5-HT neurons (Abrams et al 2005;Singewald and Sharp 2000) and can be blocked by 5-HT 2C receptor antagonists (Bagdy et al 2001;Hackler et al 2007). Similarly, although selective-5-HT reuptake inhibitors (SSRIs) can reduce clinical symptoms in the spectrum of depression and anxiety disorders following several weeks of treatment (Feighner and Boyer 1991;Kent et al 1998), SSRIs rapidly increase extracellular 5-HT in the DRN (Rutter et al 1995), and symptom exacerbation, especially an increase in anxiety, is often reported during the onset of clinical treatment with SSRIs (Feighner and Boyer 1991;Goldstein and Goodnick 1998;Masand and Gupta 1999;Nutt and Glue 1989;Pohl et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Santos et al, 2006. The ability of SB 242084 to antagonize the anxiogeniclike effects of mCPP were associated with a significant attenuation of neural activation in the amygdala (as well as the hippocampus and hypothalamus, but not mPFC) (Hackler et al, 2007). Finally, the aforementioned anxiety-like phenotype in SERT knockout mice is associated with a significant increase in 5-HT2C-R binding density in the amygdala (Li et al, 2003).…”
Section: -Ht2c Receptorsmentioning
confidence: 80%
“…Treatment with the non-specific serotonin receptor agonist mchlorophenylpiperazine (mCPP) has potent anxiogenic effects in rodent and man alike (Griebel, 1995;Menard and Treit, 1999;Millan, 2003;Murphy et al, 1986). Selective blockade of 5-HT2C-Rs with compounds such as SB 242084, either systemically or in the amygdala, is sufficient to prevent mCPP-induced (and in some cases, spontaneous or stress-induced) rodent anxiety-like behavior (Campbell and Merchant, 2003;Cornelio and Nunes-de-Souza, 2007;Graeff et al, 1996;Griebel, 1995;Hackler et al, 2007;Harada et al, 2006Harada et al, , 2007Kennett et al, 1996;Martin et al, 2002;Millan, 2003). Systemic treatment with SB 242084 also blocks the enhancement of conditioned fear produced by acute SRI treatment (Burghardt et al, 2004) (cf.…”
Section: -Ht2c Receptorsmentioning
confidence: 99%
“…mirtazapine or agomelatine (Cremers et al 2004;see Millan 2003), possibly by stimulating neurogenesis, as well as that of atypical antipsychotics Herrick Davis et al 2000). 5-HT2CR are expressed in the amygdala, and fMRI data have demonstrated that 5-HT 2C R agonists lead to its neuronal activation (Hackler et al 2007). Other therapeutic indications relate to obesity and possibly epilepsy Brennan et al 1997;Heisler et al 1998;2007a; as observed in the first series of receptor transgenic mice and later with 5-HT2CR selective ligands (Venzi et al 2016;Bagdy et al 2007;Jakus et al 2003;Isaac 2005).…”
Section: The Modern Era: Therapeutic Considerationsmentioning
confidence: 99%